Peran Aktor Politik: Revisi UU KPK 2019 Terhadap Demokrasi Indonesia - Priyudha, Fuan Yuniar; Safira, Alisa; Layyina, Tsalitsa Haura; Cindy, Cindy; Fatkhuri, Fatkhuri (Universitas Semarang, 2025)
The revision of the Corruption Eradication Commission Law No. 10 of 2019 sparked widespread protests, prompting this study to examine the role of political actors in the legislative process. Focusing on the law’s revision, the research analyzes its impact on Indonesia's democracy and highlights interactions among legislative, executive, and societal powers in combating corruption. The findings reveal that political actors significantly shape laws, affecting the independence and effectiveness of anti- corruption bodies like the Corruption Eradication Commission and influencing the integrity of Indonesia’s democratic system. The study also recommends collaboration between NGOs and both state and non-state actors. Such partnerships foster broader participation from domestic stakeholders, ensuring policies are more responsive to societal needs and challenges. This approach emphasizes the importance of inclusive governance in strengthening anti-corruption efforts and democratic resilience in Indonesia.